THE PRACTICES OF CHRISTIAN PREACHING. ESSENTIALS FOR EFFECTIVE PROCLAMATION - M. Laubscher (Acta Theologica)
A review of Alcántara, J.E. (Grand Rapids, MI: Baker Academic, 2019) 214 pp. ISBN: 978-0-8010-9866-6 (R403)